THE USE OF NATURAL DISASTER NEWS TEXT IN MODELLING STAGE TO COMPOSE NEWS ITEM TEXT: AUTHENTIC MATERIAL IN THE SECOND STAGE OF GENRE-BASED APPROACH - Azis, Abdul (English Education and Applied Linguistics Journal (EEAL Journal), 2023)
This study aims to investigate how the news item texts composed by students are based on a natural disaster news text, and how they respond to the use of natural disaster news text as a learning media to compose news item text. Based on these aims, this study uses a qualitative study by means of observation, document analysis, and questionnaire. Data collection was carried out on students twelfth grade from one of the Vocational High Schools in Garut, West Java. The results of the observation showed that under the direction of the teacher there are four steps that students took in composing news item text based on a natural disaster news text: 1) students understand the social function, linguistic elements, and structure of the news item text, 2) students open a web news link about natural disaster, 3) students write down the information they get from reading news on the web, 4) students compose a news item text based on the information. Based on the results of document analysis, it showed that the news item text composed by students fulfills the aspects of writing news item text. In addition, based on the results of the questionnaire, it showed that students gave positive responses to the use of authentic material in the form of natural disaster news texts in learning to compose news item texts. Therefore, as an effort for students to achieve the goals of learning English successfully, it is hoped that teachers can use authentic materials as learning media in the classroom.